C1‐Symmetric 1, 2‐Diaminobicyclo[2.2.2]octane Ligands in Copper‐Catalyzed Asymmetric Henry Reaction: Catalyst Development and DFT Studies. Issue 2 (15th January 2018) - Milbeo, Pierre; Moulat, Laure; Didierjean, Claude; Aubert, Emmanuel; Martinez, Jean; Calmès, Monique
Abstract : Chiral tetra‐ and bidentate ligands derived from the ( R )‐1, 2‐diaminobicyclo[2.2.2]octane scaffold were synthesized, and the influence of the N, N′ ‐substituents of the ligand on the catalytic activity of their corresponding copper(II) complexes toward the nitroaldol reaction was investigated. Among them, the complex generated in situ by the interaction of the ( R )‐ N, N′ ‐bis(1‐naphthylmethyl)‐1, 2‐diaminobicyclo[2.2.2]octane ligand with Cu(OAc)2 proved to be the most effective for the asymmetric Henry reaction of nitromethane with various aldehydes to provide β‐nitro alcohols in moderate to good yields and good enantioselectivity (up to 86 %). In an attempt to rationalize the factors that control enantiodifferentiation, the most stable geometries of this C 1 ‐symmetric bicyclic copper ligand complex and the plausible transition structures of the nitroaldol reaction were investigated by DFT calculations. Abstract : The C 1 ‐symmetric ( R )‐ N, N′ ‐bis(1‐naphthylmethyl)‐1, 2‐diaminobicyclo[2.2.2]octane ligand in combination with Cu(OAc)2 is an efficient catalyst for the asymmetric Henry reaction of nitromethane with various aldehydes. DFT calculations of the optimized conformations of the complex and the most stable transition states support preferential formation of S products, in agreement with experiments.